2005
DOI: 10.1080/10253890500495244
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation-induced changes in the hypothalamic–pituitary–adrenal axis in the rat

Abstract: Social isolation of rats both reduces the cerebrocortical and plasma concentrations of 3a-hydroxy-5a-pregnan-20-one (3a,5a-TH PROG) and 3a,5a-tetrahydrodeoxycorticosterone and potentiates the positive effects of acute stress and ethanol on the concentrations of these neuroactive steroids. We now show that social isolation decreased the plasma level of adrenocorticotropin (ACTH), moreover, intracerebroventricular administration of corticotropin releasing factor (CRF) induced a marked increase in the plasma cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
71
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(83 citation statements)
references
References 43 publications
12
71
0
Order By: Relevance
“…Following the activation of the HPA axis, the anterior pituitary secretes ACTH and the adrenal cortex secretes Cor in a few minutes to affect the behavior and neuroendocrine activities associated with the stress. Therefore, ACTH and Cor are often considered as the most classic and important indicators in studying stress (16,17). In the present study, the serum ACTH and Cor levels increased in the HE group, which indicated that the HPA axis of rats was activated in the process of exposure.…”
Section: Discussionsupporting
confidence: 53%
“…Following the activation of the HPA axis, the anterior pituitary secretes ACTH and the adrenal cortex secretes Cor in a few minutes to affect the behavior and neuroendocrine activities associated with the stress. Therefore, ACTH and Cor are often considered as the most classic and important indicators in studying stress (16,17). In the present study, the serum ACTH and Cor levels increased in the HE group, which indicated that the HPA axis of rats was activated in the process of exposure.…”
Section: Discussionsupporting
confidence: 53%
“…Similar to abuse-prone HR rats, described earlier, isolated animals have an overactive stress axis (Serra et al, 2005). Basal corticosterone is higher in IC than in EC rats, and the amphetamine-stimulated increase in corticosterone is greater in IC rats (Stairs et al, 2011).…”
Section: Psychosocial Influences and Abused Drugsmentioning
confidence: 61%
“…On the other hand, a single injection of Aβ1-42 (25 pmol/rat) into the hippocampal dentate gyrus of rats transiently induces cognitive decline without appreciable changes in behavior and locomotor activity , suggesting that the dose of Aβ1-42 and its injection site is critical for Aβ1-42 pathophysiology. Social isolation changes the HPA axis activity in the experimental animals (Serra et al, 2005), followed by behavioral abnormality such as aggression (Blanchard et al, 2001;Backström and Winberg, 2013). BPSD-like symptoms may be facilitated by social isolation in Aβ1-42-injected adult mice.…”
Section: Discussionmentioning
confidence: 99%